MEASUREMENT OF SERUM T3, T4 AND TSH FOR THE DIAGNOSIS OF THYROID DYSFUNCTION BY EMPLOYING ELISA METHODOLOGY - Rehman, Muhammad Abdul; Ashraf, Muhammad; Khan, Faiz Ahmed (Journal of Ayub Medical College Abbottabad, 1999)
Thyroid hormone profile was determined by ELISA method in 593 clinically suspected patients of thyroid disorders attending Bahawal Victoria Hospital Bahawalpur during 1988- 1995. 402 (67.7%) Patients proved euthyroid, 110 (18.6%) hyperthyroid and 81 (13.7%)) hypothyroid. The results revealed measurable thyrometabolic disturbances and the measurement of total serum thyroxine using thyrotrophic hormone (TSH) were the most useful in vitro tests for assessing thyroid status.